Entrepreneurship in China : the Emergence of the Private Sector - Atherton, Andrew; Newman, Alex. (London : Taylor and Francis, 2017)
"The Chinese economy has grown faster for a longer period than any other economy in the world. It is now the second, and will soon become the largest, global economy. This is an astonishing transformation of a country that in the late 1970s was one of the poorest in Asia. Central to this economic miracle has been the emergence of a private sector of entrepreneurs who have started and grown businesses of all sizes and types. This book explores these wealth creators and builders of China's new economy, and offers guidance on the best ways to work with China's entrepreneurs and their growing businesses. Entrepreneurship in China looks at the dynamic and changing nature of entrepreneurship, and the need for entrepreneurs to refine, adapt and evolve their approaches within an uncertain, fast-changing and volatile environment. This book examines the distinctive and particular context of China for entrepreneurs, and offers insights into how entrepreneurship has emerged as the driver of China's economy. This book will benefit business people, policy makers and researchers seeking to understand Chinese entrepreneurship and offers guidance to practitioners interested in working with private Chinese businesses."--Provided by publisher.
Formal sources of financing -- Microfinance -- Accessing external financing -- Notes -- 7. Chinese business culture and entrepreneurship -- Introduction -- Philosophical and ideological influences on Chinese culture -- Key dimensions of Chinese culture -- Holistic approaches to the study of Chinese culture -- Geographical and generational diversity -- Influence of culture on the business practices adopted by Chinese entrepreneurs -- Conclusion -- Notes -- 8. Dealing with the government -- Introduction -- The nature of government in China -- The five-year plan as a key planning framework for the state -- Enterprise policy in China -- Creating the right conditions for entrepreneurship -- Innovation and high-tech businesses -- Relations between entrepreneurs and the government -- Corruption and expropriation by officials -- 'Guanxi' relationships between officials and entrepreneurs -- The political roles and significance of entrepreneurs in China -- Notes -- 9. Doing business with Chinese entrepreneurs -- Introduction -- The importance of local knowledge -- The guanxi factor: networks and relationships in China -- Doing business with Chinese entrepreneurs -- Understanding Chinese business culture -- Developing and sustaining relationships -- Developing a successful presence in China -- Dealing with the environment around you -- A final, brief caution -- Notes -- 10. The future of entrepreneurship in China -- Introduction -- Key challenges facing private entrepreneurship -- Key sectors for growth of private entrepreneurship -- The future of entrepreneurship in China -- Conclusion -- Notes -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship -- China; Business enterprises -- China; China -- Economic conditions -- 2000-